Gerakan Cegah Diabetes: Pemeriksaan Gula Darah dan Sosialisasi Pola Hidup Sehat - Arum Kusuma Putri; Emma Ismawatie; Yulia Ratna Dewi; Laela Siti Musrikatun (Gayaku Publisher, 2025)
Diabetes Mellitus (DM) is non-communicable diseases (NCDs) that is a problem in the world. DM is a chronic metabolic disorder characterized by high-blood sugar levels. Support a healthy lifestyle with Early detection of DM and checking the current blood sugar (GDS). Uncontrolled GDS levels will cause complications in the body's organs. The method used is socialization with lecturer and discussion as well as checking the current blood sugar (GDS) at Balai RW 3 Dukuh, Ngemplak. The number of participants in this community service was attended by 11 participants. The results of this service 82% normal, 18% upnormal and average of 148.36 mg/dL (normal GDS, <200mg/dL). The result if education on management of DM, the community was anthusiastic and able to answer several questions during the discussion session.